Reassessment of the potential applications of Eu3+-doped Y2O3 photoluminescent material in ceramic powder form - Mayrinck, Caroline de; Santos, Daniela Pereira; Ribeiro, Sidney José Lima [UNESP]; Schiavon, Marco Antonio; Ferrari, Jefferson Luis (Elsevier B.V., 2014)
The preparation of Y2O3 doped with different amounts of Eu3+ ions obtained via a precipitation method using oxalic acid as precursor is reported here. The precursors were calcined at different temperatures to obtain the polycrystalline ceramic materials in order to verify the influence of temperature on the photoluminescence emission properties of the materials. The efficient incorporation of Eu3+ ions in Y2O3 host matrix was verified by X-ray diffraction. Based on the diffractograms obtained, using Scherrer's equation the increase of the crystallite size as a function of annealing temperature was verified. All materials obtained showed intense photoluminescence emission in the red region (similar to 611.5 nm), assigned to the f-f intraconfigurational transition of the Eu3+ ions. The CIE chromaticity diagrams were built based on the photoluminescence emission spectra with X and Y coordinates being 0.672 and 0.325, respectively, indicating the pure color emission of the material. The materials obtained are excellent absorbers in the UV-vis region (bellow 250, around similar to 394 and similar to 463 nm) with intense emission in the red region (similar to 611.5 nm). Two lifetime values are observed indicating that the Eu3+ ions are located in at least two sites of symmetry, C-2 and S-6. The lifetime values obtained are on the order of ms, being relatively long and interesting for contribution to solar cell efficiency improvement. The fact that these materials absorb ultraviolet radiation very well, resulting in intense emission in the red region, make them excellent candidates to for applications in solar cells. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Photoluminescence; Europium; Yttrium oxide; Ceramic; Solar cells